2020
DOI: 10.1371/journal.pone.0230042
|View full text |Cite
|
Sign up to set email alerts
|

Read-the-game: System for skill-based visual exploratory activity assessment with a full body virtual reality soccer simulation

Abstract: We present a novel virtual reality (VR) system to measure soccer players' read-the-game ability. Read-the-game is a term that encompasses a conglomerate of visual exploratory behavioral patterns and cognitive elements required to make accurate in-game decisions. Our technological approach in the Sports Science domain focuses on the visuomotor component of targeted skill development in a VR simulation because VR is a powerful perception-action coupling training solution for visuomotor coordination due to its hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 43 publications
0
9
1
Order By: Relevance
“…This result is in agreement with Jordet's [14] study of three elite midfielders, which found that so few scans lasted in excess of one second, referred to as long searches, that the results became inconsequential. In comparison, a recent study on scanning behavior in football using VR simulations focused on scans that lasted longer than one second, which the authors referred to as long exploratory activity [34]. While VR has the potential to create realistic simulations, our results show that scanning usually lasts much less than one second.…”
Section: Plos Onecontrasting
confidence: 53%
“…This result is in agreement with Jordet's [14] study of three elite midfielders, which found that so few scans lasted in excess of one second, referred to as long searches, that the results became inconsequential. In comparison, a recent study on scanning behavior in football using VR simulations focused on scans that lasted longer than one second, which the authors referred to as long exploratory activity [34]. While VR has the potential to create realistic simulations, our results show that scanning usually lasts much less than one second.…”
Section: Plos Onecontrasting
confidence: 53%
“…It should be noted that this IVR exercise required the participants to complete smooth pursuit eye movements, in response to an object moving in the 3-dimensional visual field, while coordinating the movement of their head/neck and activating a manual controller. An exercise such as this may encourage the use and development of visual exploratory activity (VEA) during the performance of soccer, which is an important ability for on-field success [ 9 ]. This may be an exercise to consider continuation of training across an athletic season to boost performance.…”
Section: Discussionmentioning
confidence: 99%
“…A burgeoning area of innovation in sports is the use of three-dimensional extended realities (XR) to provide athletes with novel training environments [ 9 , 10 ]. XR includes immersive virtual reality (IVR), where a user is only able to see and interact with a virtual environment, and augmented reality (AR), where the virtual environment is overlaid upon the real-world environment, and the user can see and interact with both.…”
Section: Introductionmentioning
confidence: 99%
“…Experts also showed quicker anticipation and decision-making processes. Most recent research conducted by Ferrer et al examined the read-the-game skills of soccer players in VR [ 27 , 54 ]. According to the authors this ability encompasses VEA, necessary for accurate in-game decision-making [ 55 ].…”
Section: Background and Related Workmentioning
confidence: 99%
“…Even though it could be shown that inertial sensors can be used for assessing athletes exploratory behavior in different sport situations [ 24 , 25 ], little research has been conducted using HMD integrated sensors to derive performance measures [ 27 , 28 ]. Specifically, to the best of our knowledge, no work investigates the assessment of VEA based on head movement characteristics under the condition of realistic dynamic VR-based soccer scenarios.…”
Section: Introductionmentioning
confidence: 99%